2009
DOI: 10.1038/nm.1925
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2–dependent induction of vitamin A–metabolizing enzymes in dendritic cells promotes T regulatory responses and inhibits autoimmunity

Abstract: Immune sensing of a microbe occurs via multiple receptors. How signals from different receptors are coordinated to yield a specific immune response is poorly understood. We demonstrate that the different pathogen recognition receptors, TLR2 and dectin-1, recognizing the same microbial stimulus, stimulate distinct innate and adaptive responses. TLR2 signaling induced splenic dendritic cells (DCs) to express the retinoic acid (RA) metabolizing enzyme Raldh2 and IL-10, and to metabolize vitamin A and stimulate Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
288
4
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(310 citation statements)
references
References 51 publications
16
288
4
2
Order By: Relevance
“…However, in infection models, TLR2 deficiency has been associated with increased IL-17 production in inflammatory sites (24,25), suggesting that other influences of inflammation and infection may affect how different TLR control T cell responses. TLR2 engagement has also been associated with increased Treg expansion in vivo (20,33,46,54), although this TLR2-mediated effect was due to direct ligation of TLR2 on Tregs (20,33). In our system, where TLR2-mediated effects were due to ligation of TLR2 on APC, we did not observe up-regulation of FoxP3 by naive Agspecific CD4 T cells following antigenic priming with the TLR2 agonist (data not shown).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, in infection models, TLR2 deficiency has been associated with increased IL-17 production in inflammatory sites (24,25), suggesting that other influences of inflammation and infection may affect how different TLR control T cell responses. TLR2 engagement has also been associated with increased Treg expansion in vivo (20,33,46,54), although this TLR2-mediated effect was due to direct ligation of TLR2 on Tregs (20,33). In our system, where TLR2-mediated effects were due to ligation of TLR2 on APC, we did not observe up-regulation of FoxP3 by naive Agspecific CD4 T cells following antigenic priming with the TLR2 agonist (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…We found similar results with both HA-and OVAspecific systems (data not shown). We also analyzed whether TLR engagement promoted Treg differentiation, given its known regulatory effects in vivo (33,46), but we did not observe up-regulation of FoxP3 expression by Ag-specific CD4 T cells primed with Ag in the presence of LPS or Pam3C (data not shown). These results indicate that TLR2 agonist priming promotes expansion of CD4 T cells producing IL-2 and IL-17, while TLR4 agonist priming results in Th1 effector generation.…”
Section: Differential Cytokine Profile Of Tlr2-vs Tlr4-primed Cd4 T Cmentioning
confidence: 97%
“…Apart from the effect of exogenous IL-2, it has been suggested that the suppressive capacity of Tregs is abolished by proinflammatory cytokines produced by APC in response to TLR ligands (12)(13)(14)(15)(16)(17)(18). TLRs are pattern recognition receptors, which are expressed in APC but also in different subsets of T lymphocytes (19)(20)(21).…”
Section: Cd25mentioning
confidence: 99%
“…GM-CSF (4) and RA (4)(5)(6)(7)(8) are pivotal factors to induce mouse DCs to express retinal dehydrogenase (RALDH)2, which is encoded by the aldehyde dehydrogenase 1 family, member A2 (ALDH1A2) gene and converts retinal to RA. IL-4 (4, 9) and TLR ligands (2,4,5,(10)(11)(12) augment the expression of RALDH2. These studies have presented a model that appropriately stimulated CD103 + DCs in gut-associated tissues produce RA and thus induce gut-homing Treg cells, resulting in maintaining immune homeostasis in the intestine in mice.…”
mentioning
confidence: 99%